Tumor associated neutrophils promote the metastasis of pancreatic ductal adenocarcinoma. Issue 10 (2nd October 2020) - Lianyuan, Tao; Gang, Li; Ming, Tao; Dianrong, Xiu; Chunhui, Yuan; Zhaolai, Ma; Bin, Jiang
ABSTRACT: The aim of this study was to investigate the role of tumor-associated neutrophils (TANs) in the metastasis of pancreatic ductal adenocarcinoma (PDAC), to explore the regulation of TANs, and to determine the mechanisms governing the metastasis of PDAC. The correlation between neutrophils and the patient's clinical pathological data was first evaluated. Then, the effects of neutrophils on the invasion of PDAC were analyzed using a combination of conditioned media, direct and indirect coculture of human peripheral blood neutrophils, and PDAC cell lines (Panc-1, MiaPaCa-2 and AsPC-1). The cytokines secreted by neutrophils were detected through ELISA. TAN density was significantly correlated with poor metastasis-free survival ( P < .05). Through coculture, it was found that the effect of neutrophils on pancreatic cancer cells was dependent on concentration, and a high concentration of neutrophils showed a lethal effect, while a low concentration of neutrophils primarily promoted the migration ability of cancer cells. The results of the wound-healing assay, the Transwell invasion assay, and laser confocal microscopy confirmed the promoting effect and indicated that the effect of neutrophils toward cancer cells may function indirectly by releasing a series of cytokines. The results of ELISA show that this effect may be achieved through the secretion of a large amount of TNF-α and TGF-β1 by neutrophils. Our study indicated that neutrophils may increase the metastasis of PDAC by releasing a series of cell cytokines, such as TNF-α and TGF-β1.